Antitumor Effects and Related Mechanisms of Ethyl Acetate Extracts of Polygonum perfoliatum L. - Li, Qinglin; Fu, Xiaoxuan; Ge, Xinyang; Tao, Feng; Huang, Ping; Ge, Minghua; Jin, Hongchuan (Frontiers in Oncology, 2019)
Polygonum perfoliatum L belongs to the Polygonaceae, one of the Chinese herbal medicines. In this study, the anti-tumor effect of Polygonum perfoliatum L extracts was tested in vitro and in vivo, and the ethyl acetate extract with good anti-tumor activity and low toxicity was screened to obtain the anti-tumor active component (abbreviated as PEC). Furthermore, the anti-tumor effects and mechanisms of PEC such as inducing apoptosis and blocking proliferation cycle of tumor cells as well as the growth inhibition curve were investigated by in vitro cell experiments. In vivo experiments were carried out to investigate the effects and mechanisms of PEC in suppressing tumor growth, anti-angiogenesis and regulating immune function. The results showed that PEC had a certain growth inhibitory effect on a variety of tumor cells with different sensitivities, which displayed dose-effect and time-effect relationships. PEC has significant in vivo anti-tumor effects on H22 liver cancer, S-180 sarcoma and SGC-7901 in nude mice.